Analysis of pre-competitive anxiety of Brazilian young swimmers (Acta Scientiarum. Health Sciences, 2019)
This study analyzed the level of state-anxiety of swimming athletes based on sex, category, competitive specialty, competitive level and competitive experience. Participants were 178 male (n = 105) and female (n = 73) swimmers with mean age of 15.51 ± 1.9 years at regional, national and international levels. The Competitive State Anxiety Inventory-2 (CASI-2) was used as instrument. Data analysis was conducted using the independent Student’s t-test, Mann-Whitney, Kruskal-Wallis and Spearman correlation. The results showed higher levels of self-confidence in males (p = 0.02) and higher levels of cognitive anxiety in females (p = 0.019). Among the competitive specialties, there were differences between levels of cognitive anxiety (p = 0.045) and self-confidence (p = 0.041) of swimmers. Differences were also observed in levels of cognitive anxiety (p = 0.049), somatic anxiety (p = 0.001) and self-confidence (p = 0.047) between swimming competition levels. It was concluded that male swimmers are more self-confident and less anxious than female swimmers and there are different levels of self-confidence and types of anxiety for different competitive specialties and ranking of competitions.